Influence of Geographic Origin and Plant Source on Physicochemical Properties, Mineral Content, and Antioxidant and Antibacterial Activities of Moroccan Propolis - Naoual El Menyiy; Meryem Bakour; Asmae El Ghouizi; Soukaina El Guendouz; Badiaa Lyoussi (International Journal of Food Science)
This research is aimed at determining the physicochemical properties (resin, wax, balsams, pH, moisture, ash, and mineral contents) of propolis samples collected from different geographical areas in Morocco, as well as evaluating the antioxidant and antibacterial activities of these samples. The results showed the following values for physicochemical analysis: resin (17.42-58.01%), wax (21.31-70.12%), balsam (0.27-2.12%), pH (3.7-5.3), moisture (1.02-3.65%), and ash (0.72-5.01%). The phenolic and flavone/flavonol contents of samples were ranged between 6.74 mg FAE/g and 149.13 mg FAE/g and between 1.19 mg QE/g and 108.11 mg QE/g, respectively. The sample P3 presented also the strongest radical scavenging activity toward DPPH, ABTS free radicals, and FRAP assay with IC50 values of 0.021, 0.026, and 0.042 mg/mL, respectively. All propolis samples showed significant inhibitory effects against all tested microorganisms with MICs ranging from 0.28 mg/mL to 1.12 mg/mL for Gram-negative strains and from 0.002 mg/mL to 1.12 mg/mL for Gram-positive strains. A strong correlation was found between resin, total phenolic compounds, flavones/flavonols, and antioxidant activity. Linear discriminant analysis revealed that the samples studied were divided into two groups which were differentiated by the data of antioxidant activity, mineral contents, and antibacterial activity. It can be concluded that the physicochemical properties, mineral content, and biological activities of Moroccan propolis depend on their geographical and botanical origin.